2016
DOI: 10.1097/cej.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Prelabor cesarean delivery and early-onset acute childhood leukemia risk

Abstract: The long-term impact of cesarean delivery (CD) on the health of the offspring is being explored methodically. We sought to investigate the effect of birth by (a) prelabor and (b) during-labor CD on the risk of early-onset (≤3 years) acute lymphoblastic leukemia (ALL), specifically of its prevailing precursor B (B-ALL) subtype. A total of 1099 incident cases of ALL (957 B-ALL), 131 of acute myeloid leukemia (AML), and their 1 : 1 age-matched and sex-matched controls, derived from the Nationwide Registry for Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
16
1
3
Order By: Relevance
“…One study distinguished between emergency and prelabour caesarean delivery and reported null associations for caesarean delivery overall and for prelabour caesarean delivery in children diagnosed at age 0-14 years, but reported moderate positive associations for children aged 0-3 years between ALL—particularly B-cell ALL—and both all-caesarean deliveries and prelabour caesarean delivery. 19 By contrast, no association was identified with emergency caesarean delivery. 19 Finally, one study investigated common ALL and reported a positive association between this subtype and caesarean delivery, especially in Hispanic people.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…One study distinguished between emergency and prelabour caesarean delivery and reported null associations for caesarean delivery overall and for prelabour caesarean delivery in children diagnosed at age 0-14 years, but reported moderate positive associations for children aged 0-3 years between ALL—particularly B-cell ALL—and both all-caesarean deliveries and prelabour caesarean delivery. 19 By contrast, no association was identified with emergency caesarean delivery. 19 Finally, one study investigated common ALL and reported a positive association between this subtype and caesarean delivery, especially in Hispanic people.…”
Section: Discussionmentioning
confidence: 98%
“…19 By contrast, no association was identified with emergency caesarean delivery. 19 Finally, one study investigated common ALL and reported a positive association between this subtype and caesarean delivery, especially in Hispanic people. 20 Our findings suggest that prelabour caesarean delivery increases risk of ALL.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…During the period 1996–2013, 1496 confirmed incident leukaemia cases aged 0–14 years old were notified by the network of Nationwide Registry for Childhood Hematological Malignancies and Brain Tumors (NARECHEM‐BT) collaborators in all six paediatric haematology‐oncology departments across Greece. Details on the NARECHEM‐BT case–control study have been described elsewhere . In the course of the study, interviews with the guardians of 192 children were not conducted for short intervals in two of the collaborating departments due to purely administrative reasons that are not likely to bias the results.…”
Section: Methodsmentioning
confidence: 99%